Compound C Protects Against Cisplatin-Induced Nephrotoxicity Through Pleiotropic Effects - Li, Fanghua; Sun, Anbang; Cheng, Genyang; Liu, Dong; Xiao, Jing; Zhao, Zhanzheng; Dong, Zheng (Frontiers in Physiology, 2020)
AICAR (Acadesine/AICA riboside) as an activator of AMPK, can protect renal tubular cells from cisplatin induced apoptosis. But in our experiment, the dorsomorphin (compound C, an inhibitor of AMPK) also significantly reduced cisplatin induced renal tubular cells apoptosis. Accordingly, we tested whether compound C can protect cisplatin-induced nephrotoxicity and the specific mechanism.Here, we treated Boston University mouse proximal tubular cells (BUMPT-306) with cisplatin and/or different dosages of AICAR (Acadesine/AICA riboside) or compound C to confirm the effect of AICAR and compound C in vitro. The AMPK-siRNA treated cells to evaluate whether the protective effect of compound C was through inhibiting AMPK. Male C57BL/6 mice were used to verify the effect of compound C in vivo. Both compound C and AICAR can reduce renal tubular cells apoptosis in dose-dependent manners, and compound C decreased serum creatinine and renal tubular injury induced by cisplatin. Mechanically, compound C inhibited P53, CHOP and p-IREα during cisplatin treatment. Our results demonstrated that compound C inhibited AMPK, but the renal protective effects of compound C were not through AMPK. Instead, compound C protected cisplatin nephrotoxicity by inhibiting P53 and endoplasmic reticulum (ER) stress. Therefore, compound C may protect against cisplatin-induced nephrotoxicity through pleiotropic effects.